Cultura de aprendizagem e desempenho organizacional em emissoras de TV cearenses - Silva, Antonia (2013)
Organizational culture can be understood as a dynamic phenomenon constantly created and played by the interaction between people, shaped by leadership behavior and a set of structures, routines, rules and norms that guide and restrict (SCHEIN, 1984). The main purpose of this research is to analyze how is the relationship between learning culture and organizational performance on TV broadcasters of Ceará state, in the perception of its employees. The study of the culture of learning and performance of these firms, that are in constant process of changes and innovations, justified by contributing to an area that has been little explored in the Brazilian literature. The theoretical basis of this study are the factors of organizational learning culture and organizational performance (EASTERBY-SMITH; BURGOYNE; ARAÚJO, 2001; YANG, 2003; SCHEIN, 1984, 2009; MARSICK E WATKINS, 2003; REBELO; GOMES, 2008; LIMA; ARRUDA, 2012). This is a quantitative and descriptive survey conducted by TV broadcasters together to Jangadeiro, TV Verdes Mares and TV União, located in the city of Fortaleza, state of Ceará. It was applied a simplified version of the questionnaire "Dimensions of the Learning Organization Questionnaire (DLOQ-A)" developed by Yang (2003), which includes the process of learning at the individual, group and organizational. The questionnaire contains 27 closed questions with Likert scale (1 - Almost never to 6 - Almost always) applied in printed form, along with 95 employees of the stations surveyed. For data analysis, we used SPSS version 19. After analyzing the results, it can be inferred that the factors of learning culture with the highest explanatory power of financial performance were: the individual level, Opportunity for Lifelong Learning (OLL) and, at the organizational level, Development of Systemic View Organization (DSVO), Systems to Capture and Share Learning (SCSL) and Incentives for Strategic Leadership for Learning (ISLL). The factors of learning culture with the highest explanatory power of organizational gain were: the individual level, Opportunity for Lifelong Learning (OLL); group level, Collaboration and Team Learning (CTL) and, at the organizational level, Empowerment and Responsibility (ER) and the Development of a Systemic Vision of the Organization (DSVO). The regression coefficient ( ) on the learning culture was 0.763. This implies that, if a unit increase in the learning culture, organizational performance in the TV stations will be increased by 0.763 unit. It is noteworthy that the significance of the model is high, can be seen with the value of the F statistic (142.214). Finally, it was found that the learning culture has a strong influence on organizational performance in TV stations surveyed, the perception of its employees.